Effects of STAR and TAR types nonlinearities on order selection criteria - Venus, Khim-Sen Liew; Terence, Tai-leung Chong (University Library of Munich, Germany, 2003)
This paper investigates via a simulation study the effects of nonlinearities on several commonly used order selection criteria. The most important finding of this study is that SIC, FPE, HQC and BIC perform considerably well in estimating the true autoregressive order, even in the presence of STAR or TAR nonlinearity. Thus we conclude that these criteria may be safely applied to determine the true order of STAR or TAR process.